Heterogeneous Fenton-Like Catalysis of Electrogenerated H2O2 for Dissolved RDX Removal - Compton, Patrick; Dehkordi, Nazli Rafei; Knapp, Michael; Fernandez, Loretta A.; Alshawabkeh, Akram N.; Larese-Casanova, Philip (Frontiers in Chemical Engineering, 2022)
New insensitive high explosives (IHE) pose great challenges to conventional explosives manufacturing wastewater treatment processes and require advanced methods to effectively and efficiently mineralize these recalcitrant pollutants. Oxidation processes that utilize the fundamental techniques of Fenton chemistry optimized to overcome conventional limitations are vital to provide efficient degradation of these pollutants while maintaining cost-effectiveness and scalability. In this manner, utilizing heterogeneous catalysts and in-situ generated H2O2 to degrade IHEs is proposed. For heterogeneous catalyst optimization, varying the surface chemistry of activated carbon for use as a catalyst removes precipitation complications associated with iron species in Fenton chemistry while including removal by adsorption. Activated carbon impregnated with 5% MnO2 in the presence of H2O2 realized a high concentration of hydroxyl radical formation - 140 μM with 10 mM H2O2 - while maintaining low cost and relative ease of synthesis. This AC-Mn5 catalyst performed effectively over a wide pH range and in the presence of varying H2O2 concentrations with a sufficient effective lifetime. In-situ generation of H2O2 removes the logistical and economic constraints associated with external H2O2, with hydrophobic carbon electrodes utilizing generated gaseous O2 for 2-electron oxygen reduction reactions. In a novel flow-through reactor, gaseous O2 is generated on a titanium/mixed metal oxide anode with subsequent H2O2 electrogeneration on a hydrophobic microporous-layered carbon cloth cathode. This reactor is able to electrogenerate 2 mM H2O2 at an optimized current intensity of 150 mA and over a wide range of flow rates, influent pH values, and through multiple iterations. Coupling these two optimization methods realizes the production of highly oxidative hydroxyl radicals by Fenton-like catalysis of electrogenerated H2O2 on the surface of an MnO2-impregnated activated carbon catalyst. This method incorporates electrochemically induced oxidation of munitions in addition to removal by adsorption while maintaining cost-effectiveness and scalability. It is anticipated this platform holds great promises to eliminate analogous contaminants.